2011
DOI: 10.1200/jop.2011.000259
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Information Systems for Electronic Chemotherapy Medication Administration

Abstract: Overall, the configured systems facilitate compliance with the ASCO/ONS guidelines and improve the consistency of documentation and multidisciplinary team communication. Our success has prompted us to deploy this infrastructure in our outpatient chemotherapy infusion centers, a process that is currently underway and that will require a few unique considerations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 8 publications
2
18
0
Order By: Relevance
“…This result is congruent with the positive results of other studies that have assessed some EMR functions for cancer care, mainly in improving documentation and standardising procedures in parts of the care process, such as order entry systems, to support the chemotherapy process in medical oncology (Adelson et al, 2014;Brockstein et al, 2011;Harshberger et al, 2011;Kukreti et al, 2014;Levy et al, 2011;Meisenberg et al,2014;Pirnejad et al, 2013) and electronic checklists (record and verify software) in radiation oncology (Albuquerque et al, 2011;Chua et al, 2010;Goldwein, 2011;Kirkpatrick et al, 2013). The users' attitudes, as measured by both the survey and the interviews, were quite positive in the post-period, and the new EMR was considered better than the former system.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…This result is congruent with the positive results of other studies that have assessed some EMR functions for cancer care, mainly in improving documentation and standardising procedures in parts of the care process, such as order entry systems, to support the chemotherapy process in medical oncology (Adelson et al, 2014;Brockstein et al, 2011;Harshberger et al, 2011;Kukreti et al, 2014;Levy et al, 2011;Meisenberg et al,2014;Pirnejad et al, 2013) and electronic checklists (record and verify software) in radiation oncology (Albuquerque et al, 2011;Chua et al, 2010;Goldwein, 2011;Kirkpatrick et al, 2013). The users' attitudes, as measured by both the survey and the interviews, were quite positive in the post-period, and the new EMR was considered better than the former system.…”
Section: Discussionsupporting
confidence: 87%
“…The literature nevertheless reports several positive results. For instance, in medical oncology, benefits have been demonstrated in terms of compliance with guidelines (Adelson et al, 2014;Levy et al, 2011;Meisenberg, Wright, & Brady-Copertino, 2014), documentation completeness Harshberger et al, 2011;Levy et al, 2011), fewer problematic orders (Adelson et al, 2014;Brockstein et al, 2011;Kukreti, Cosby, Cheung, & Lankshear, 2014;Meisenberg et al, 2014), improved multidisciplinary team communication (Levy et al, 2011), lighter workloads (Kukreti et al, 2014;Pirnejad, Gao, Reddingius, Rijnevevld, & Bal, 2013) and faster turnaround times (Pirnejad et al, 2013). In radiation oncology, benefits have also been reported in terms of better documentation (Albuquerque, Miller, & Roeske, 2011;Goldwein, 2011;Kirkpatrick et al, 2013), real-time generation of outcome data (Chua et al, 2010), standardised procedures (Albuquerque et al, 2011) and the number of times that physicians were called to the treatment unit (Albuquerque et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…A handful of studies describe the methods used for implementing a cpoe system for chemotherapy 6,14,19,28 . Harshberger et al 29 reported improved user satisfaction and better completeness of chemotherapy orders and documentation after a cpoe system was implemented to replace paper-based charts at a large multi-site teaching hospital, and Brockstein et al 30 described the impact of the cpoe implementation at the same institution on documentation, communication, operations, quality improvement, and research.…”
Section: Resultsmentioning
confidence: 99%
“…Among the proposed approaches to prevent medication errors, bar code technology retained our attention because of positive feedback from nuclear medicine [13] and other medical fields. Indeed, this technology has been successfully tested in drug dispensation [14], cancer care [15,16] and drug administration in neonatal units [17] and intensive care units [18]. This paper reports an approach towards improving radiopharmaceutical supply chain safety by implementing bar code technology and evaluating employee activity in terms of overtime, overheads (due to overtime, investment, supplies) and radiation overexposure.…”
Section: Introductionmentioning
confidence: 98%